2017
DOI: 10.1182/blood-2016-06-721878
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of multiparametric flow cytometry in AL amyloidosis at diagnosis and at the end of first-line treatment

Abstract: Key Points• The monotypic and polytypic PC compartments assessed by MFC are prognostic in AL amyloidosis.• MFC may play a role in the definition of hematologic response to treatment.Multiparametric flow cytometry (MFC) in amyloid light-chain (AL) amyloidosis has not been widely adopted and, consequently, there is little information on its clinical relevance. We studied 173 patients with AL amyloidosis who underwent MFC immunophenotyping of bone marrow sample at diagnosis and 82 patients at the end of the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 17 publications
1
33
0
3
Order By: Relevance
“…The clinical relevance of flow cytometry-based MRD assessment and its predictive value on organ response in AL amyloidosis is of growing interest. [6][7][8][9][10] Organ response is a crucial outcome for patients with this disease, yet the precise mechanisms of organ dysfunction and how hematologic response following treatment affects organ recovery are not well understood. Generally, a deep hematologic response (hemVGPR or better) is required for organ response, but even those who achieve hemCR can endure persistent organ dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical relevance of flow cytometry-based MRD assessment and its predictive value on organ response in AL amyloidosis is of growing interest. [6][7][8][9][10] Organ response is a crucial outcome for patients with this disease, yet the precise mechanisms of organ dysfunction and how hematologic response following treatment affects organ recovery are not well understood. Generally, a deep hematologic response (hemVGPR or better) is required for organ response, but even those who achieve hemCR can endure persistent organ dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In AL amyloidosis, an MFC method using surface markers adopted from multiple myeloma was shown to detect aberrant PCs at the time of diagnosis with high sensitivity and the presence of ,0.1% monotypic PCs by MFC after initial treatment to predict longer survival. 6,7 Subsequent studies indicated longer progression-free survival and possibly improved organ response with MRD negativity. [8][9][10] With small sample sizes in these previous investigations, we sought to elucidate the clinical relevance of MFC-based MRD assessment in patients with hemCR.…”
Section: Introductionmentioning
confidence: 99%
“…A rapid reduction of light chains to very low levels with treatment results in organ improvement and better survival . We have previously demonstrated that lack of residual bone marrow monotypic plasma cells using flow cytometry (sensitivity ≥1 × 10 −4 ) is associated with superior outcomes . There is limited data on outcomes in AL amyloidosis using next generation MRD assessment methods (next generation flow cytometry [NGF] or next generation sequencing [NGS]), which are currently endorsed for MRD response evaluation for multiple myeloma by the International Myeloma Working Group .…”
Section: Introductionmentioning
confidence: 99%
“…MS detected residual disease among AL amyloidosis patients in hematologic CR, not only in the context of negative blood and urine IFE and serum FLC but also in the context of a negative bone marrow employing sixcolor flow cytometry, which has approximately one order of magnitude less sensitivity than the next-generation flow cytometry and two orders of magnitude than the next-generation sequencing. Current consensus response criteria exclude bone marrow as part of hematologic response 6,7 , but we included bone marrow response because emerging data demonstrate that patients with a negative bone marrow by flow cytometry fare better than those without [13][14][15][16][17][18] . Despite the limited sample size, there was a very significant difference in progression-free survival between the MS-positive and -negative patients.…”
Section: Discussionmentioning
confidence: 99%